The LATTICE Study: Design of a pilot feasibility randomized controlled trial of lithium to delay cognitive decline in mild cognitive impairment - Ariel G. Gildengers; Tamer S. Ibrahim; Xuemei Zeng; Howard J. Aizenstein; Salem K. Alkhateeb; Stewart J. Anderson; Cong Chu; Jihui L. Diaz; James E. Emanuel; Thomas K. Karikari; Jinghang Li; Oscar L. Lopez; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Interest has grown in lithium's neuroprotective properties in neurodegenerative illnesses. We discuss the design, rationale, and implementation of a pilot feasibility, double‐blind, randomized placebo‐controlled trial (RCT) examining whether lithium can delay cognitive decline in older adults with mild cognitive impairment (MCI). METHODS The study launched in September 2017. The goal was to enroll 80 community‐dwelling participants ≥ 60 years with MCI into an RCT in which they would participate for 2 years with baseline and follow‐up assessment of cognition, brain imaging, and plasma‐based biomarkers. Participants were randomized to lithium or placebo (1:1). RESULTS We enrolled 80 MCI older adults into the RCT. Baseline characteristics included a mean (standard deviation) age of 72 (7.7) years with 35 male and 45 female participants. Seventy‐five participants had positron emission tomography imaging for amyloid beta (Aβ), and 66 completed 7T magnetic resonance imaging. Twenty‐one participants were Aβ+ and 54 were Aβ–. DISCUSSION The study successfully enrolled 80 participants into an RCT examining whether lithium delays cognitive decline. The main study results will be forthcoming. Clinical Trial Registration NCT03185208. Highlights Eighty adults ≥ 60 years with mild cognitive impairment entered a placebo‐controlled randomized controlled trial evaluating lithium's neuroprotective properties. Participants were followed for 2 years with baseline and follow‐up evaluations at 1 and 2 years that included neurocognitive assessment, ultra‐high‐field structural neuroimaging, positron emission tomography imaging for amyloid beta and tau, and plasma‐based biomarkers. Study results will be forthcoming.